Ochrona interesu dewelopera przez prawo odstąpienia od umowy deweloperskiej i modyfikację stosunku umownego na podstawie klauzuli rebus sic stantibus - Pliszka, Natalia (PRAWO i WIĘŹ, 2024)
Nowadays, the prevailing views in society regarding the improper practices of real estate developers have led to the formation of a negative perception of this professional group. The necessity to write the following work arose from the fact that most representatives of the doctrine, or scientific authors focus in their considerations on strengthening the protection of the purchaser of premises as the weaker party. Even the legislator himself did not hide his assumptions when creating the law and giving it the title Law on the Protection of the Rights of the Purchaser of a Dwelling or Single-Family House. In the author’s opinion, it is necessary to ensure the protection of each of the parties to the development contract and to create a study to draw attention to the lawful ways of pursuing claims in the cases of improper behavior on the part of the purchaser. The work will address issues related to the developer’s ability to apply the rebus sic stantibus clause and the contractual right of withdrawal. The attention will also be paid to the limits and possible consequences of not applying the principle of pacta sunt servanda, which is still known from Roman times.